2016
DOI: 10.5539/jas.v8n10p63
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Transfer into Chicken Gonads by Combining Transposons with Polyethylenimine

Abstract: Transposon mediated transfection is a promising, safe, and convenient way to generate transgenic chicken compared with virus-mediated technology and the in vitro modification of primordial germ cells (PGCs). To establish a simple method for in vivo transfection of chicken PGCs, we applied four different transposon systems (PB, SB, Tol2, and ZB) to investigate the gene transfer efficiency of chicken gonads via direct injection of a mixture of transposon and transposase plasmids and transfection reagent (polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…We found that the proportion of Venus-positive gonads in all three injected genotypes was about 92–100%. This is consistent with other studies using reporter carrying PGCs 41 , 42 . The Venus-transfected PGCs do not lose their ability to migrate from the peripheral blood into the developing gonads of the embryos.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the proportion of Venus-positive gonads in all three injected genotypes was about 92–100%. This is consistent with other studies using reporter carrying PGCs 41 , 42 . The Venus-transfected PGCs do not lose their ability to migrate from the peripheral blood into the developing gonads of the embryos.…”
Section: Discussionsupporting
confidence: 93%